The complete mitochondrial genome of Macridiscus multifarius (Bivalve, Veneridae). Issue 1 (2nd January 2019) - Fu, Zeqin; Ye, Yingying; Feng, Jiantong; Guo, Yahong; Li, Jiji; Guo, Baoying; Lv, Zhenming
Abstract: Herein, we first determined the complete mitochondrial genome of Macridiscus multifarius in this study. The circular mitochondrial genome is 20, 248 bp in length, consisting of 12 protein-coding genes, 22 tRNA genes and 2 ribosomal RNA genes. The nucleotide composition is 28.6% of A, 39.3% of T, 10.4% of C and 21.7% of G. In 12 protein-coding genes, Cytb, atp6, and nad6 start with ATG, nad1, 3 and COX2 with GTT, COX3 and nad4 with ATT, and COX1 and nad5 with ATA. For the stop codon, seven genes with TAA, nad3, 4, 5 and COX3 with TAG, atp8 ends with AAA. The phylogenetic tree was constructed based on 12 protein-coding genes of 11 species using the Neighbour-joining method, and the result showed that the M. multifarius was closed to the Ruditapes philippinarum . The mitochondrial genome would be helpful for the study of population genetic and phylogenetic analysis of Marcidiscus.